2002
DOI: 10.1177/07419325020230040701
|View full text |Cite
|
Sign up to set email alerts
|

Self-Determination

Abstract: Self-determination is now widely recognized in the literature as a best-practice procedure in the education of students with disabilities, particularly regarding facilitating students' transition from high school to adult life. But what do teachers know about how to facilitate student self-determination? In this study, special educators and university professors were surveyed to determine what teachers know about self-determination, what the primary source of their information about self-determination is, what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(6 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Similarly, as students progress through adolescence, greater attention may be focused on equipping them with the decision-making skills needed to plan for future careers, education, and community participation after high school (Lusk & Cook, 2009). Fourth, consistent with previous surveys of general and special educators (Thoma, Nathanson, Baker, & Tamura, 2002;Thoma, Pannozzo, Fritton, & Bartholomew, 2008;Wehmeyer et al, 2000), we found that paraprofessionals reported varied awareness of the self-determination concept. Specifically, nearly one fifth of paraprofessionals (19.7%) said they were not at all familiar with the concept of self-determination, 54.3% said they were somewhat familiar, and 26.0% said they were very familiar.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, as students progress through adolescence, greater attention may be focused on equipping them with the decision-making skills needed to plan for future careers, education, and community participation after high school (Lusk & Cook, 2009). Fourth, consistent with previous surveys of general and special educators (Thoma, Nathanson, Baker, & Tamura, 2002;Thoma, Pannozzo, Fritton, & Bartholomew, 2008;Wehmeyer et al, 2000), we found that paraprofessionals reported varied awareness of the self-determination concept. Specifically, nearly one fifth of paraprofessionals (19.7%) said they were not at all familiar with the concept of self-determination, 54.3% said they were somewhat familiar, and 26.0% said they were very familiar.…”
Section: Discussionsupporting
confidence: 83%
“…What might account for the fairly modest ratings of instructional frequency and self-determination opportunities at these schools given the high importance administrators placed on their instruction? Although our instrument did not ask administrators to speak to the form instruction actually took in their schools, prior research suggests these skills might be addressed more incidentally (versus explicitly) within the school curriculum (Mason et al, 2004; Thoma, Nathanson, Baker, & Tamura, 2002). If true, administrators may not be aware of the full extent to which these component skills are being addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Trainor (2007) encouraged educators to engage in strengthbased transition planning and instruction, taking into consideration the sociocultural interactions of students with disabilities and their postschool environments. According to Thoma, Nathanson, Baker, and Tamura (2002), it is important to remember that the achievement of self-determination requires not only that people with disabilities develop their own inner resources, but that society support and respond to them as well. Bambara, Cole, and Koger (1998) further explained it this way: "Enhancing self-…”
Section: Life-long Value Of Self-determination Instructionmentioning
confidence: 99%
“…We also affirm Chambers and colleagues' ( 2007) call for more research on the roles that embedded opportunities, environmental responsiveness, and ecological and environmental variables in school settings play in the development of self-determination. Chambers et al (2007) and other researchers (e.g., Agran, Snow, & Swaner, 1999;Grigal et al, 2003;Thoma et al, 2002; have claimed that few teachers actually implement instruction to promote the self-determination of students with disabilities. Chambers and colleagues' review of the literature yielded several studies showing that teachers do not feel they have sufficient training or information to implement instruction that would promote self-determination (e.g., Thoma et al; Wehmeyer et al).…”
Section: Challenges Of Schoolsmentioning
confidence: 99%